The Role of Accounting Policy in the Enterprise Management System (Economics and region, 2019)
The article describes the essence, purpose of accounting policy and its management orientation. The aspects of accounting process that influence the order of accounting policy formation are investigated: methodical, technical and organizational. The stages of accounting policy formation that are advisable to follow at the enterprise are presented. Investigating the existing problems in the formation of accounting policies of the company, the following ways are proposed to solve them: to improve the regulatory framework, since inconsistencies between the acts prevent the enterprise in the formation of effective accounting policies; bring national standards closer to international standards; consider in detail in the normative documents the nature, advantages and disadvantages of various elements of accounting policies. The importance of subordination of accounting policy elements to the objectives of the management process is proved.
Keywords: accounting policy; accounting policy order; accounting; management accounting